Chiral Non‐Planar Oligophenylenes Bridged by Urea Linkage: Synthesis through Intramolecular Direct Arylation, Chiroptical Behavior, and Theoretical Investigation. Issue 10 (4th March 2019) - Takagi, Koji; Hirano, Yuto; Mikami, Koichiro; Kikkawa, Shoko; Azumaya, Isao
Abstract : The intramolecular direct arylation of N, N′ ‐dihexyl‐ N ‐(2‐bromophenyl)‐ N′ ‐phenylurea using palladium catalyst gave BPU in 75 % yield. Longer terphenyl compound (TPbU ) was likewise prepared. Other four conjugated oligomers (BPtU, BPU‐1Np, BPU‐2Np, and BPU‐Ant ) were synthesized from BPU in short reaction steps. From the X‐ray crystallography, BPtU with the thiourea skeleton was suggested to have a quasi C=N double bond character. Each enantiomer was optically resolved on chiral HPLC to show mirroring Cotton effects and monosignate CD patterns. The enantiomeric excess ( ee .) values were evaluated by HPLC, from which BPU and TPbU exhibited comparable racemization energy barriers (Δ G ‡ rac = 23.3 kcal mol –1 and 23.4 kcal mol –1 ). The racemization energy barrier of BPtU was considerably high (Δ G ‡ rac = 30.1 kcal mol –1 ) likely due to the quasi C=N double bond character. On the other hand, BPU‐2Np and BPU‐Ant having the π‐conjugated system exhibited Δ G ‡ rac of 23.8 kcal mol –1 and 24.0 kcal mol –1, respectively. These experimental results were well explained by theoretical analyses. Abstract : Six non‐planar and urea‐bridged conjugated oligomers were synthesized through palladium‐catalyzed intramolecular direct arylation and their chiroptical properties were investigated in detail.